Regulation of Survivin Gene Expression in Stem Cell and Cancer Stem Cells and Emphasis Approach - Nihayah, Silviatun; Wanandi, Septelia Inawati (http://dharmais.co.id/, 2025)
Background: Gene expression regulation is a method that cells utilize to enhance or decrease the output of specific genes (proteins or RNA). In biological and medical research such as cancer, gene expression is routinely observed. Survivin is a protein that is commonly produced in cancer cells and has the potential to be investigated. Survivin is a unique protein with two distinct roles: preventing apoptosis and regulating cell division. The inhibitory apoptosis protein (IAP) family includes the smallest member. Furthermore, Survivin is highly expressed in a variety of somatic stem cell types as well as human embryonic stem cells. Comparing most cancer cells to normal tissues, survivin is also present in higher amounts. This review aimed to examine the properties of survivin, how it is expressed in cancerous and normal stem cells, how it affects proliferation or apoptosis, and how to block their expression. Methods: The literature on the regulation of survivin expression in cancer cells and stem cells that was published in English between 2014 and 2024 is reviewed in this study. For articles, we looked through PubMed, Scopus, and the Google Scholar database. In order to support the theories, publications from before 2014 were also tracked down.Results: Molecular mechanism studies indicate that survivin participates in numerous signaling pathways, including MAPK, STAT3, b-catenin, Wnt, Notch, and others, and also controls the progression of the cell cycle and cytokinesis. Several elements, such as signaling pathway blockage siRNA technology, and CRISPR/Cas9 system have been discovered to aid in the induction of cancer cell death. Conclusion: Survivin is linked to several cancer survival-related pathways, contributing to carcinogenesis. Its expression is associated with treatment resistance, tumor development, and poor prognosis.